The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/pd.5015
|View full text |Cite|
|
Sign up to set email alerts
|

Fetal right aortic arch: associated anomalies, genetic anomalies with chromosomal microarray analysis, and postnatal outcome

Abstract: A right aortic arch is associated with 22q11.2 deletion syndrome in approximately 5% of cases, and, therefore, prenatal testing, preferably using CMA, should be offered. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
(43 reference statements)
3
18
0
1
Order By: Relevance
“…Given the selective nature of our data, we did not comment on the incidence of RAA, but the prevalence of CVR was 82%. The most frequent forms of CVR were RAA/LPDA/ALSA and DAA, which is consistent with previous reports [13][14][15] . We found one case of RAA with ALIA and one with ALSA origin obstruction, both of which have been reported previously to be rare [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Given the selective nature of our data, we did not comment on the incidence of RAA, but the prevalence of CVR was 82%. The most frequent forms of CVR were RAA/LPDA/ALSA and DAA, which is consistent with previous reports [13][14][15] . We found one case of RAA with ALIA and one with ALSA origin obstruction, both of which have been reported previously to be rare [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…Considering all 55 pregnancies, including the 10 excluded which did not have postnatal assessment of AA anatomy, karyotype was abnormal in five (9%), which is consistent with values reported previously. Duplication of 11p15.1 in a fetus with RAA was described for the first time in this study, while other copy number imbalances have been reported previously. XYY karyotype associated with CVR has been described previously in one case.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Most studies detect associated cardiac, noncardiac, and genetic anomalies in a proportion of these cases supporting detailed examination and possible molecular testing. Most also report a 22q11.2 deletion in approximately 5% of those undergoing genetic testing (D'Antonio, Khalil, Zidere, & Carvalho, ; Evans et al, ; Galindo et al, ; O'Mahony, Hutchinson, McGillivray, Nisbet, & Palma‐Dias, ; Peng, Xie, Zheng, Zhou, & Lin, ; Razon et al, ; Vigneswaran et al, ; Wojtowicz et al, ), which is substantially lower than that observed in the post‐natal study (McElhinney, McDonald‐McGinn, et al, ) but consequential nonetheless. Two studies specifically reported on the rare fetal diagnosis of a left‐sided aortic arch with an aberrant right subclavian artery (Ranzini, Hyman, Jamaer, & van Mieghem, ; Rembouskos et al, ).…”
Section: The 22q112 Deletion Syndrome In the Chd Populationmentioning
confidence: 99%